Work-related well-being. Issue 1 (5th February 2016) - Soh, Melinda; Zarola, Antonio; Palaiou, Kat; Furnham, Adrian
This study aimed to investigate the different dimensions of well-being (namely, work engagement, job satisfaction, and psychological stress) and possible predictors such as personality and perceived organizational support. A cross-sectional survey design was used, with a sample of 490 ambulance personnel in the United Kingdom. Significant correlations were found between the dimensions of job satisfaction, engagement, and stress. The results also supported a hierarchical model with job satisfaction, stress, and engagement loading onto one higher order factor of work well-being. Emotional stability and perceived organizational support were identified as significant predictors of well-being. The findings suggest the importance of measuring the work-related well-being of ambulance personnel holistically and present perceived organizational support as a possible area for interventions to improve well-being.